Ethnic Nationalism and Secessionist Agitations in Post-Colonial Africa: A Comparative Study of Biafra and Ambazonia - Fatai-Abatan, Abiodun; Adeleke, Amos Babarinde; Akinyetun, Tope Shola; Kunmavo, Afolabi Tagbe (Department of International Relations, Hasanuddin University, 2025)
Secessionist agitation in Africa remains a recurring challenge in the postcolonial era, largely shaped by ethnic nationalism, identity politics, and systemic marginalization. These movements are often rooted in grievances stemming from political exclusion, economic inequality, and historical injustices against minority ethnic groups. The Indigenous People of Biafra (IPOB) in Nigeria and the Ambazonia separatist movement in Cameroon are examples of such struggles, seeking autonomy in response to perceived domination by the majority ethnic groups. While the IPOB’s agitation traces its origins to the 1967 declaration of Biafra and the subsequent civil war, the Ambazonian crisis is a consequence of the longstanding marginalization of Anglophone Cameroonians in a Francophone-dominated state structure. A qualitative research method that interrogates secondary data sources, including historical archives, policy documents, and scholarly literature was adopted. The findings indicate that these movements are not merely relics of colonial legacies and ethnic grievances but are also shaped by contemporary socio-economic challenges, systemic exclusion, and state repression. Moreover, the security implications extend beyond Nigeria and Cameroon, posing significant threats to the regional stability in West Africa. Therefore, inclusive governance, equitable resource distribution, and diplomatic interventions by regional and international organizations are essential for mitigating tensions. Meanwhile, political restructuring, economic reforms, and sustained dialogue remain critical pathways for achieving sustainable peace and stability in Nigeria and Cameroon.